Macroeconomic Implications of the Transition to Inflation Targeting and Capital Account Liberalization in Romania - Gueorguiev, Nikolay (IMF Working Papers; Working Paper ;, 2004)
In the near future, Romania will introduce inflation targeting and fully liberalize its capital account. This paper aims to analyze, in a dynamic general-equilibrium model with sticky prices and monopolistic competition, how these two profound changes will affect the ability of monetary policy to pursue its objective of price stability. In particular, the resilience of the current and future monetary policy regimes to shocks is evaluated against two welfare criteria: a standard central bank loss function containing the deviations of inflation, output, and the real exchange rate from their equilibrium values, and the compensating variation measure of Lucas (1987).